Synthesis and Characterization of Stoichiometric Spinel-LiMn2O4 - T. Y.S Panca Putra; D Deswita; A. Insani; H. Mugiraharjo; E. Sukirman; A.K. Jahja; T.H. Priyanto; S. Lee; T. Kamiyama (PPIKSN-BATAN, 2017)
In this study, spinel LiMn2O4 powder was synthesized from LiOH.H2O and MnOx by conventional and mechanical alloying (MA) methods, followed by heat treatment at 800 °C in O2 for four hours with cooling to room temperature in the furnace at 60 °C/h. It is found that both samples do not show phase transition in low temperature, and this occurred for different reasons. In the MA sample, the presence of Fe as contamination increased the Mn valence and hindered the occurrence of phase transition. The conventional sample does not show phase transition at low temperature due to stoichiometric content, without any contamination. In general, the absence of phase transition occurred due to synthesis condition employed in this study.